Own experience of primary mediastinal B-large cell lymphoma treatment - M. A. Vernyuk; N. G. Tyurina; O. A. Pavlova; A. M. Chervontseva; N. V. Zhukov (Онкогематология)
Due to the relative low incidence of primary mediastinal B-large cell lymphoma (PM BLCL) optimal approaches to its treatment is still not well developed. Possibility to improve PM BLCL clinical outcomes by intensifying induction chemotherapy (CT) and the use of rituximab, the usefulness of high-CT with autologous stem cells transplantation (autologous HSCT) and radiotherapy (RT) is currently being studied.The purpose of this study was to evaluate the efficacy and tolerability of induction therapy MACOP-B with or without rituximab in patients with PM BLCL. 34 patients with PM BLCL, received MACOP-B (n = 10) or R-MACOP-B (n = 24) in P.A. Herzen Moscow Research Institute of Oncology during January 2006 and August 2013, were included in the study. 28 patients (82.4 %) achieved partial/complete remission after MACOP-B ± rituximab completing. In case of insufficient response (large residual tumor) or primary resistance patients received the second line chemotherapy and/or autologous HSCT. 25 patients received radiotherapy for residual tumor mass after CT completion. After completion of full treatment program remission was achieved in total of 32 patients (94.1 %): complete remission in 27 (79.4 %) and partial remission in 5 (14.7 %). Relapse occurred in 3 patients (8.8 %). With a median follow-up of 36.5 months, 3-year disease-free survival was 93 %, eventfree survival – 75 % and overall survival – 90 %. Thus, the “MACOP-B ± rituximab” program was highly effective and acceptable tolerated in PM BLCL patients. The necessity of auto-HSCT and radiotherapy remains debatable.